Optimizing the synthesis of Fe/Al (Hydr)oxides-Biochars to maximize phosphate removal via response surface model. (10th November 2019) - Peng, Yutao; Sun, Yuqing; Sun, Runze; Zhou, Yaoyu; Tsang, Daniel C.W.; Chen, Qing
Abstract: Highly efficient and cost-effective adsorbents for phosphate (P) recovery are the key to control eutrophication and recover phosphorous from waste streams to enhance food production. This study assembled waste biomass (corn stalk, almond shell, and dairy manure)-derived biochars with Fe/Al (hydr)oxides through co-precipitation method. The fabricated biochar composites presented excellent performance for the adsorption of P due to good amounts of surface area, pore volume, and reactive surface hydroxyl sites. Response surface methodology (RSM) was applied to optimize the production conditions of the Fe–Al (hydr)oxides-biochars for maximizing the P removal. The effects of three key independent variables, i.e., Fe 3+ concentration (0.2–1.0 mol L −1 ), Al 3+ concentration (0.2–1.0 mol L −1 ), and mass-to-volume ratio (0.05–0.20 g mL −1 ) on the P removal were investigated. The synthesized composites outperformed other sorbents for the P removal, suggesting the synergistic effects of Fe/Al (hydr)oxides and biochar support. These results offer valuable insights to develop high-performance biochar-based composites for green and sustainable environmental remediation. Graphical abstract: Image 1 Highlights: Biomass types determined physiochemical characteristics of Fe/Al-modified biochar. Synthesis conditions could be optimized via RSM based on P removal capacity. High P adsorption capacity of 215.1 mg (PO4 3− )/g was obtained. Multiple P removal mechanisms involved complexation, adsorption, and precipitation.